Rejection in heart transplantation for cardiac sarcoidosis mimicking idiopathic giant cell myocarditis: long-term follow-up. Issue 4 (April 2019) - Di Nora, Concetta; Miani, Daniela; Sponga, Sandro; Livi, Ugolino
Abstract : N/A: Heart transplantation is a life-saving therapy for some patients admitted for acute myocarditis. However, controversial exists about the major risk of rejection following heart transplantation in specific types of myocarditis. Because of relatively few data on the post heart transplant outcomes, we report the long-term follow-up of a 39-year-old patient with a previous history of ulcerative colitis, which rapidly worsened heart failure until an emergency heart transplant in 2004. The clinical course was complicated by many episodes of rejection; lastly, after the development of severe cardiac allograft vasculopathy, re-heart transplantation was needed. The main findings of this case are: 1) inflammatory aetiology should always be suspected in patients with concomitant autoimmune disease that developing rapidly progressing heart failure; 2) patients with inflammatory myocardial disease undergoing heart transplantation should also undergo strict immunological surveillance; 3) the option of performing the re-heart transplant in a patient with a so complex management in the first one could be uncertain, but in this case the young age and lack of noncardiac comorbidities were effective to favour the survivor after two immunologically so challenging heart transplantation. Abstract : Supplemental Digital Content is available in the text